Kostensensible Leitlinien Evidenzbasierte Leistungssteuerung für eine effiziente und gerechte Gesundheitsversorgung - Marckmann, Georg (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2015)
Medical innovations and demographic change will further exacerbate the financial situation in the German healthcare system in the coming years. The evidence-based allocation of the limited funds available will therefore become increasingly important. From an ethical perspective, allocation decisions should be based on clearly defined procedures and criteria. So far, however, there are no concrete approaches on how this explicit performance control can be implemented in practice. The book provides an overview of the results of the interdisciplinary research association ""Allocation"", which for the first time examined the possibilities and limits of explicit performance management in two selected practical areas (interventional cardiology and intensive care medicine). Two exemplary cost-sensitive guidelines have been developed that enable an evidence-based balance between efficiency and justice. The legal requirements for such an explicit benefit management in statutory health insurance were examined in detail. Healthcare professionals and patients were asked for their assessments of the strengths and weaknesses of the cost-sensitive guidelines.